2007
DOI: 10.1007/s00192-007-0355-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pregnancy and childbirth on female rats’ urethral nerve fibers

Abstract: This study aims to evaluate the urethral nerve fibers of adult female rats during pregnancy and after vaginal birth, cesarean section or simulated birth trauma. For immunohistochemical analysis of nerve fibers, 70 female rats were distributed in seven groups of ten female rats: group 1, control; group 2, pregnant; group 3, cesarean section; group 4, vaginal birth; group 5, virgin female rats with simulated birth trauma; group 6, cesarean section followed by simulation of birth trauma; and group 7, vaginal birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
2
9
1
Order By: Relevance
“…However, although not statistically significant, Figure clearly showed that MYOD1 and MYOG gene expression were lower in the EST group compared with untreated rats. Electric current potentially improves muscle repair and the evaluation moments (7 and 30 days after trauma) failed to detect the exact moment of this mechanism . The results by Russo et al corroborate our findings.…”
Section: Discussionsupporting
confidence: 88%
“…However, although not statistically significant, Figure clearly showed that MYOD1 and MYOG gene expression were lower in the EST group compared with untreated rats. Electric current potentially improves muscle repair and the evaluation moments (7 and 30 days after trauma) failed to detect the exact moment of this mechanism . The results by Russo et al corroborate our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Even though there are differences between multiparous and nulliparous rats, VD is not innocuous in multiparous animals. It increases the percent of rats with urine leakage and the damage to urethral striated muscle and nerve fibers (45,46), from which we conclude that the VD model in nulliparous animals is suitable to mimic prolonged vaginal parturition, with the consideration that in some variables, the magnitude of the VD-induced damage may differ between nulliparous vs delivery groups.…”
Section: 56)mentioning
confidence: 82%
“…The anterior location of the fetal head afforded by a wider pelvis might directly damage the urethra or urethral supports, similar to the vaginal delivery-induced urethral changes seen in previously published animal models. (16, 17) Alternatively, trauma from the delivery may unmask preexisting poor urethral function that, prior to delivery of the newborn, was compensated for by urethral support and/or pelvic floor functioning. Interestingly, despite a two-fold higher rate of visible levator ani defects in the incontinent primiparas than the primiparous controls, we find no association between the rates of these muscle defects and the subpubic angle, suggesting that any birth trauma promoted by a wider subpubic angle is not reflected in the visible levator ani defects noted on MRI.…”
Section: Discussionmentioning
confidence: 99%